2018
DOI: 10.3390/ijerph15102096
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contaminants and Congenital Heart Defects: A Re-Evaluation of the Evidence

Abstract: Congenital heart defects (CHDs) are a common birth defect of largely unknown etiology, with high fetal and neonatal mortality. A review of CHDs and environmental contaminant exposure found that meta-analyses showed only modest associations for smoking, vehicle exhaust components, disinfectant by-products and proximity to incinerators, with stronger results from the newer, larger and better quality studies masked by the typical absence of effect in older studies. Recent studies of exposure to agricultural pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 90 publications
3
34
1
8
Order By: Relevance
“…The association between paternal smoking and birth defects in the offspring is unclear, although that of maternal habits on offspring is well recognised. [1][2][3][4][5][6][7] Exposure to paternal cigarette smoke affects the genomic and epigenomic components of sperm via the aryl hydrocarbon receptor (AHR), nuclear factor-E2 related factor 2 (NRF2) and mitogen-activated protein kinase (MARK) pathways, which influences the offspring's development in animal models. 8 Several clinical studies provide evidence of paternal smoking contributing to birth defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between paternal smoking and birth defects in the offspring is unclear, although that of maternal habits on offspring is well recognised. [1][2][3][4][5][6][7] Exposure to paternal cigarette smoke affects the genomic and epigenomic components of sperm via the aryl hydrocarbon receptor (AHR), nuclear factor-E2 related factor 2 (NRF2) and mitogen-activated protein kinase (MARK) pathways, which influences the offspring's development in animal models. 8 Several clinical studies provide evidence of paternal smoking contributing to birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…First, potential confounders, such as maternal and paternal geographical and genetic factors, environmental exposure and folic acid supplements, which are related to genetic mutation and impaired methylation causing differences in the incidence of birth defects, should be considered. 1,2,12,13 Paternal smoking and alcohol consumption, which often co-exist, have similar toxic effects on germ cells and fetal development, via germ cell mutation, genetic imprinting and epigenetic pathways. To investigate the causal relation between paternal smoking and birth defects, details of paternal and maternal smoking and alcohol consumption, such as exposure timing, frequency and behaviour change after conception, must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of approximately 20% of CHDs can be linked to known causes, while the rest of cases are the result of complex interactions between genetic, lifestyle, and environmental factors 4,5 . Previous studies explored that maternal antibiotic use (adjusted odds ratio [aOR] = 3.96; 95% CI: 1.78‐8.79), maternal alcohol consumption (aOR = 2.14; 95% CI: 1.64‐2.80), age (aOR = 1.94; 95% CI: 1.12‐3.34), past induced abortion (aOR = 1.58; 95% CI: 1.12‐2.22), education of parents (aOR = 1.47; 95% CI: 1.28‐1.69), the use of assisted reproduction techniques for conception (aOR = 1.45; 95% CI: 1.20‐1.76), higher maternal body mass index (aOR = 1.32; 95% CI: 1.21‐1.43), parity (aOR = 1.18; 95% CI: 1.03‐1.34), and maternal smoking (aOR = 1.11; 95% CI: 1.02‐1.21) may all increase the risk of CHDs, while maternal folate intake (aOR = 0.42; 95% CI: 0.21‐0.86) may have a protective effect 6‐11 . Other studies have also confirmed occupation of parents as a possible causative factor for the development of CHDs.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly identified occupations include painters, janitors, food service workers, electricians, health care personnel, or plastic workers 5,12,13 . As endocrine disrupting chemicals are often used by people employed in these areas, several studies have focused on this group of chemicals 8 …”
Section: Introductionmentioning
confidence: 99%
“…To improve crop yield, chemical fertilizer is widely used 6 . Therefore, in the process of agricultural production, people have more direct contact with pesticides and other harmful substances [6][7][8] . In addition, some non-standard small factories directly discharge factory exhaust gas and wastewater to the environment 9,10 .…”
mentioning
confidence: 99%